The Effect of Working Capital Turnover on Profitability at PT. Arwana Citra Mulia Tbk Period 2015-2022 - Hisar Pangaribuan (Fin Sinergy: Jurnal Manajemen Keuangan, 2023)
This study aims to determine the effect of working capital turnover on profitability at PT Arwana Citra Mulia Tbk for the 2015-2022 period. The method used is explanatory research. The analysis technique uses statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study the working capital turnover variable obtained an average value of 3.552%. Profitability variable obtained an average value of 8.380%. Working capital turnover has a positive and significant effect on profitability with a regression equation value Y = 1.311 + 0.002X, and a correlation coefficient value of 0.724 or having a strong relationship with a determination value of 52.4%. The hypothesis test obtained a significance of 0.042 <0.05.